Aquinas and the Jews - Hood, John Y. B., 1962- (Middle Ages series., 1995)
Hood's study contends that Aquinas's writings remain resistant to or skeptical of anti-Jewish trends in thirteenth-century theology. Aquinas sets out simply to clarify and systematize received theological and canonistic teachings on the Jews.